STRATEGIC CROSSROADS: GEOPOLITICAL DIMENSIONS OF EU–UZBEKISTAN RELATIONS (1991–2024) - Nusratulloyev Shaxzod Amonjon oʻgʻli (TADQIQOTLAR, 2025)
Abstract: This article provides a professional and data-driven analysis of political relations  between  the  European  Union  (EU)  and  Uzbekistan  from  1991  to  2024. Drawing  on  a  broad  range  of  scholarly  literature  and  official  sources,  it  traces  the evolution  of  EU-Uzbekistan  cooperation  through  stages  of  diplomatic  engagement, sanctions, strategic recalibration, and institutional partnership. Special focus is given to legal frameworks, geopolitical realignments, mutual interests, and recent diplomatic developments. It concludes by outlining the potential trajectory of the relationship amid Uzbekistan’s ongoing reforms and the EU’s evolving priorities in Central Asia.